2017
DOI: 10.1007/s00405-017-4747-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and management of vascular complications in middle ear and cochlear implant surgery

Abstract: The objective of this study is to illustrate prevention strategies and management of vascular complications from the jugular bulb (JB) and internal carotid artery (ICA) during middle ear surgery or cochlear implantation. The study design is retrospective case series. The setting is tertiary referral university hospital. Patients were included if presented pre- or intraoperative evidence of high-risk anatomical anomalies of ICA or JB during middle ear or cochlear implant surgery, intraoperative vascular injury,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Violation of the carotid canal may be managed with or without removal of the malpositioned array 19-21 . In patient 15, the tip of the array was cut and left in place in order to reduce the risk of a vascular complication 21 . Possible array misplacement strongly support the necessity of a postoperative radiological control, at least in the unusual CI cases 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Violation of the carotid canal may be managed with or without removal of the malpositioned array 19-21 . In patient 15, the tip of the array was cut and left in place in order to reduce the risk of a vascular complication 21 . Possible array misplacement strongly support the necessity of a postoperative radiological control, at least in the unusual CI cases 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The JB may be damaged during myringocentesis, tympanomeatal flap elevation, and removal of disease in hypotympanic and protympanic areas. 5 Surgical maneuvers in the regions at risk for vessel injury should be performed as last steps, after disease clearing, cavity regularization, and hemostasis. Dissection should be performed bluntly, using cottonoids soaked with epinephrine and in a medial to lateral way, avoiding pulling mucosal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in case of a vascular anomalies, some authors advocate for open mastoidectomy techniques to obtain a large surgical field to easily identify all the surgical landmarks. 5 TEES is gaining popularity almost in every field of otologic surgery, including pediatrics and lateral skull base. [6][7][8] The main advantage is the enhanced visibility of the anatomy and pathology due to wide-angled view and the capability to look around the corner which permits to explore hidden recesses, such as the retro-and hypotympanum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 A highriding jugular bulb may cover the round window or basal cochlear turn, thereby hindering access to the cochlear lumen via the standard transmastoid approach. 14 Hara et al found that reconstructed 3D-CT images were useful when surgically planning cochlear implantation in a patient exhibiting an abnormal facial nerve course; 15 3D images are optimal for assessing temporal bone anatomy, and they show the skull base and any middle-or inner-ear anomalies. 16,17 Breinbauer and Praetorius 12 described the optimal spatial orientation of insertion vectors for cochleostomy and the round window approach through 3D reconstruction of the temporal bones of 50 cochlear implant candidates (100 ears).…”
Section: B Jun S Songmentioning
confidence: 99%